Macroeconomic Determinants of South African Oil Prices: Evidence from Alternating Market Conditions - Moodley, Fabian; Pillay, Surendran (International Journal of Energy Economics and Policy, 2025)
The introduction of the adaptive market hypothesis (AMH) allows for the review of the relationship between macroeconomic variables and oil prices, such that the relationship is said to alternate with bull and bear market conditions. In an attempt to contribute to the revised literature, the study examines the influence of macroeconomy on South African (SA) oil index returns. The study incorporates six macroeconomic factors (inflation, money supply, short-term interest rates, long-term interest rates, gross domestic product (GDP), and exchange rate) and SA oil price index returns for the period February 1996 to December 2024. Using the Two-State Markov regime switching mode, the findings indicate that macroeconomic variables have an alternating effect on SA oil index returns. It is evident when macroeconomic factors have a significant effect on SA oil index returns in a bull regime, the effect is insignificant in a bear regime. Hence, SA commodity market, more especially the oil market is not efficient as proposed by the efficient market hypothesis and is better model by asymmetrical models.